Dosimetric Comparison of High Dose Rate Brachytherapy vs MR-Guided SBRT Boost for Cervical Cancer - Dincer, N.; Ugurluer, G.; Mustafayev, T. Zoto; Serkizyan, A.; Aydin, G.; Gungor, G.; Atalar, B.; Ozyar, E. (ELSEVIER IRELAND LTD, 2023)
Annual Meeting of the European-Society-for-Radiotherapy-and-Oncology (ESTRO), Vienna, AUSTRIA, MAY 12-16, 2023